Characterization of the exhaustion profile of activated carbon in industrial rum "filters" based on TGA, TD-GC/MS, colorimetry and NMR relaxometry. (June 2017) - Crespo Sariol, Harold; Maggen, Jens; Czech, Jan; Reekmans, Gunter; Reggers, Guy; Yperman, Jan; Adriaensens, Peter; Brito Sauvanell, Ángel; Carleer, Robert; Navarro Campa, José
Graphical abstract: Abstract: Spectrophotometric measurements applied on saturated granular activated carbons have been barely explored. Although Nuclear Magnetic Resonance (NMR) relaxation studies proved to be suitable to explore pore characteristics in different porous materials, characterization of granular activated carbons used in rum production have not been addressed yet. In this work, the feasibility of using NMR relaxometry and colorimetry in order to characterize the exhaustion degree of granular activated carbon (GAC) from a target rum "filter" is evaluated. Colorimetric measurements and the transverse NMR relaxation time distribution have been correlated with the amount of adsorbed organic compounds on these GAC. Samples from eight consecutive GAC layers of the rum filter have been assessed. The exhaustion profile for the rum "filter" is correlated with the colorimetric results, the 1 H NMR T2 -relaxometry measurements, the TD-GC/MS chromatograms and the CHNS-O elemental analysis. The proposed methods are not only of general use in GAC characterization but open possibilities for the rum producers to improve the management and economical use of the activated carbon at industrial scale.